PENGARUH BOOK TAX DIFFERENCES DAN ARUS KAS TERHADAP PERTUMBUHAN LABA - Windarti, Erika Ratih; Sulistiani, Dwi (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2015)
AbstractThis study aimed to obtain empirical results about the influence of book tax differences and cash flow toward the profit growth. Independent variables in this study were book tax differences which were proxied to be permanent differences and temporary differences, as well as the cash flow. Control variables used are return on assets (ROA) and the size of the company. The dependent variable was earnings growth. Method of sample selection used was the purposive sampling method and obtained samples of 27 companies. This test was using SPSS V 21 for Windows. The results showed that the permanent difference and temporary differences of the book tax differences have positive influence on the profit grouth of the company, while cash flow did not significantly influence the company’s profit growth.AbstrakPenelitian ini bertujuan untuk memperoleh hasil empiris tentang pengaruh book tax differences dan arus kas terhadap pertumbuhan laba. Variabel independen dalam penelitian ini antara lain book tax differences yang diproksikan menjadi beda permanen dan beda temporer, serta arus kas. Variabel kontrol yang digunakan adalah Return On Assets (ROA) dan ukuran perusahaan. Sedangkan variabel dependennya adalah pertumbuhan laba. Analisis data dengan menggunakan regresi berganda (Ordinary Least Square). Hasil penelitian menunjukkan bahwa beda permanen dan beda temporer dari book tax differences serta arus kas berpengaruh positif terhadap pertumbuhan laba perusahaan. ROA dan ukuran perusahaan tidak berpengaruh signifikan terhadap pertumbuhan laba.